THE EFFECT OF AUDIOLINGUAL-BASED VERSUS COMMUNICATIVE LANGUAGE TEACHING-ORIENTED TECHNIQUES ON INTERMEDIATE EFL LEARNERS’ LISTENING COMPREHENSION - Polrodi, Sepideh; Pourhosein Gilakjani, Abbas (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
This study was an investigation to find out the effect of audiolingual (ALM)-based versus communicative language teaching (CLT)-oriented techniques on Iranian intermediate EFL learners’ listening comprehension ability. To do this, sixty EFL learners in intermediate level from Shokouh Institute in Lahijan, Iran were selected randomly and assigned to two groups; namely the experimental group and control group; 30 participants in each group were selected based on their performance using the oxford placement test (OPT). A quasi-experimental design was used for this study. A listening audio text extracted from the book “Four Corners” was administered as pre-test and post-test. The researchers taught the students of both groups for 10 sessions. The CLT techniques were used as treatment in the experimental group while the control group received no treatment and just used ALM techniques. After 10 sessions, the listening passages extracted from the book “Four Corners” were administered as post-test in order to compare the results of the scores of two groups and decide about the effectiveness of the treatment. Finally, the data were analyzed via running an Independent Samples T-test and a series of Paired Samples T-tests. The results showed that Iranian EFL learners’ listening comprehension skill has been significantly improved as a result of using CLT techniques at the significance level of .05. It was concluded that the use of CLT techniques was highly effective in Iranian learners’ listening comprehension improvement.